1999
DOI: 10.1063/1.479741
|View full text |Cite
|
Sign up to set email alerts
|

On the short time motion of hydrogen-bonded molecules in supercooled water

Abstract: The short time dynamics of tagged pairs of molecules that, at the initial time, are in the first coordination shell, is investigated in supercooled liquid water at 245 K by using the molecular dynamics technique with the four-points transferable intermolecular potential of Jorgensen et al. [J. Chem. Phys. 79, 926 (1983)]. The instantaneous normal mode approach and the results of the local structure investigations are exploited to build up a correlation function of the relative displacements that represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…3͒. They are damped oscillations with amplitude of about 0.08 Å, significantly smaller than the initial pair separation ͗r 12 (0)͘ϭ2.8 Å, and frequency of 6.9ϫ10 12 Hz, about one-half of the librational frequency. 1 The oscillation persists till about 0.4 ps.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…3͒. They are damped oscillations with amplitude of about 0.08 Å, significantly smaller than the initial pair separation ͗r 12 (0)͘ϭ2.8 Å, and frequency of 6.9ϫ10 12 Hz, about one-half of the librational frequency. 1 The oscillation persists till about 0.4 ps.…”
mentioning
confidence: 90%
“…To select the relative pair orientations, the set of the Eulerian angles ϭ͕,⌿,⌽͖ in the local reference frame was used, and the total angular space of a pair, ⍀ ϭ͕ 1 , 2 ͖, was divided in subspaces ⍀ ⌫ which collect a set of distorted dimer geometries; each set is referred to as a configuration state ⌫ ͑or simply configuration or state͒. The main physical quantities concerning the translational motion are R 2 (r 0 ,⍀ ⌫ ;t)ϭ͗r 12 2 (t)͘ 0,⌫ Ϫ͗r 12 2 (0)͘ 0,⌫ and S 2 (r 0 ,⍀ ⌫ ;t) ϭ͉͗r 12 (t)Ϫr 12 (0)͉ 2 ͘ 0,⌫ , where r 12 is the intermolecular center-of-mass ͑c.m.͒ separation vector and ͗͘ 0,⌫ stands for averages over tagged pairs of molecules which, at the time tϭ0, are in the region of the configuration space characterized by the distance r 0 ϭr 12 (0) and by the orientations of the subspace ⍀ ⌫ . These functions are the extension to molecular fluids of the functions used to investigate the relative motion in monatomic fluids.…”
mentioning
confidence: 99%
“…2 If the short-time motions of the molecules were purely harmonic oscillations, ⌬B(r 0 ;t) should yield the average of the normal modes projected over the space direction R i j (0) selected by the configuration ⌫. 1,2 If nonharmonic motions give a significant contribution, one can suppose that the computed ⌬B(r 0 ;t) is the sum of the harmonic, ⌬B h (r 0 ;t), and nonharmonic, ⌬B nh (r 0 ;t), contributions:…”
Section: Molecular Dynamics Simulation and Theorymentioning
confidence: 99%
“…In Ref. 2, it has been suggested that the DOS of HB can be reproduced by Gaussian functions that arise from broadened phonon branches of the solid. To analyze the short-time dynamics we have used a damped harmonic oscillator ͑DHO͒like model.…”
Section: B the Local Oscillations At Short Timesmentioning
confidence: 99%
See 1 more Smart Citation